(untitled) (Research, Society and Development, 2023)
Objective: To identify scientific evidence in the literature about the risks of pneumonia for the elderly and its main clinical manifestations. Methodology: Integrative literature review carried out in the databases: SCIELO, LILACS and BDENF, in August 2022, with 83 articles being found using the descriptors “Elderly”, “Clinical Manifestations” and “Pneumonia” using the Boolean AND operator. Thus, only complete, free articles published in Portuguese between 2018 and 2022 were selected. Dissertations, monographs and those that did not correspond to the proposed objective were excluded. At the end, 8 articles were selected to compose the study. Results: The complications that the disease can cause for the elderly population vary according to the stages of the pathophysiology, and can mainly cause pleural effusion, lung abscess, low blood pressure, lung injury and hypothermia. In line with this, the number of elderly deaths due to pneumonia complications is directly associated with weaknesses, such as: advanced age, low immunity, physiological issues, preexisting comorbidities, hospital infections and late diagnosis. The main predisposing factors evidenced through the literature are a history of smoking, use of air conditioning, associated diseases, coronavirus infection and permanence in poorly ventilated environments. Conclusion: The accomplishment of this study showed, through the literature, the main predisposing factors for the development of pneumonia in the elderly population, as well as the clinical manifestations and complications that the disease can cause. This field of study was prioritized due to the fact that there are difficulties and gaps in knowledge about the subject in question.